Nutraceutical, Nutrition Supplements and Human Health (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue of Nutrients on "Nutraceutical, Nutrition Supplements, and Human Health" provides readers with contemporary knowledge on the role of functional foods, dietary supplements, and nutraceuticals in improving overall health and preventing chronic diseases. Various renowned international scientists, physicians, and other healthcare professionals have contributed to this compendium of excellent laboratory and clinical studies. The manuscripts provide evidence-based knowledge of nutritional compounds/functional food to improve many health conditions, including metabolic disorders, cardiovascular disease, muscle metabolism, obesity, neurological disorders, infectious diseases, aging, and cancer. All contributions were thoroughly peer-reviewed by a distinguished panel of scientists, and only highly ranked manuscripts were included to ensure the quality of contents. This book is an excellent resource for academic personnel and students in nutrition research, dietitians, physicians, and consumers.